The critical roles of miR-21 in anti-cancer effects of curcumin - Chen, Jiezhong; Xu, Tiefeng; Chen, Chen (Annals of Translational Medicine; Vol 3, No 21 (December 17, 2015): Annals of Translational Medicine, 2015)
Curcumin is a well-known phytochemical that has various anti-cancer effects. Although it has been demonstrated that curcumin can inhibit multiple signalling pathways, the exact mechanisms for its demonstrated anti-cancer effects are not fully understood. Recent studies have revealed that curcumin may affect cancer initiation and progression through regulating microRNAs (miRs). In this review, we focus on the roles of microRNA-21 (miR-21) in the anti-cancer effects of curcumin and regulatory mechanisms for the effects of curcumin on miR-21. MiR-21 mediates various effects of curcumin on cancer cells including proliferation, apoptosis, metastasis and anticancer drug resistance. Several downstream pathways of miR-21 have been identified including phosphatase and tensin homolog (PTEN)/phosphoinositide 3-kinase/protein kinase B (PI3K/Akt), programmed cell death protein 4 (PDCD4) and NF-κB pathways. Curcumin decreases miR-21 levels through both increasing miR-21 exosome exclusion from the cells and inhibiting the transcription of the miR-21 gene in the cells by binding to its promoter.